Cruel justice: three strikes and the politics of crime in America's Golden State - Domanick, Joe (University of California Press, 2004)
Kimber Reynolds : outside the daily planet -- The natural -- Justice seldom seen in America -- Mike Reynolds's world -- Mike Reynolds's law -- A menace to society -- Child of the '50s -- Roots of the backlash -- The new yellow press -- Tough love : Sue Reams and her boy -- "Weird ducks and blind fools" -- Right out of her own bedroom -- Another piercing scream -- "Guns don't kill people" -- The prince of "J" Street : Don Novey comes on board -- Polly Klaas : America's child -- Happily shaking fate's sorry hand -- Checking the weather vane -- Looking East, looking West -- Say hello to Hitler, Dahmer, and Bundy -- Pizza face -- Another Reynolds bill : "ten-twenty-life" -- Jean Valjean redux -- The more committed executioner -- Lenny, drug court, and three strikes -- The modification -- Shane and A.J. -- A "Taliban-type" law